COMPARISON OF ZONISAMIDE AND CARBAMAZEPINE MONOTHERAPY IN ADULTS WITH NEWLY DIAGNOSED PARTIAL EPILEPSY: PRELIMINARY RESULTS OF A PHASE III, RANDOMISED, DOUBLE-BLIND, NON-INFERIORITY TRIAL. Issue 11 (9th October 2013) - Baulac, Michel; Brodie, Martin
Abstract : Purpose: To compare efficacy and safety of once-daily zonisamide (ZNS) and twice-daily controlled-release carbamazepine (CBZ) monotherapy in adults with newly diagnosed partial epilepsy. Methods: Phase III, international, randomised, double-blind, non-inferiority trial, in which 583 untreated adults (18–75 years) with newly diagnosed partial epilepsy received ZNS or CBZ. Following initiation (ZNS 100 mg/day; CBZ 200 mg/day) and up-titration (to 300 and 600 mg/day, respectively), patients entered 26–78-week flexible-dosing period (200–500 and 400–1200 mg/day, respectively, according to response/tolerability). Once seizure-free for 26 weeks, patients entered a 26-week maintenance phase. Primary endpoint was proportion of patients seizure-free for ≥26 weeks. Safety/tolerability evaluation included assessment of treatment-emergent adverse events (TEAEs). Results: Overall, 161/282 (57.1%) patients randomised to ZNS and 192/301 (63.8%) patients randomised to CBZ completed the trial. 26-week seizure freedom rates were 79.4% (177/223) for ZNS vs. 83.7% (195/233) for CBZ (Per Protocol Population). Adjusted absolute treatment difference was -4.5% (95% confidence interval [CI]: −12.2, 3.1). The lower CI limit narrowly exceeded the protocol-specified −12% margin, but lower CI limit of the relative difference (−14.7%) was within the ILAE-recommended margin (−20%). In majority of patients seizure freedom was achieved at first dose level (ZNS 300 mg; CBZ 600 mg). Incidence of TEAEs was similar for ZNS (60.5%) vs. CBZ (61.7%), as was incidence of serious TEAEs (5.3% vs. 5.7%) and TEAEs leading to withdrawal (11.0% vs. 11.7%). Conclusion: Both ZNS and CBZ demonstrated high response rates and were well-tolerated in newly diagnosed partial epilepsy patients.